Omega-3 Fatty Acid Supplementation Improves Heart Rate Variability in Obese Children - Christoph Baumann; Ulla Rakowski; Reiner Buchhorn (Hindawi Limited, 2018)
Obese children and adolescents are at high risk of developing cardiovascular diseases later in life. We hypothesized that cardiovascular prophylaxis with omega-3 fatty acids could benefit them. In our study, 20 children and adolescents (mean body mass index percentile: 99.1; mean age: 11.0 years) underwent two ambulatory 24 h Holter electrocardiography (ECG) recordings (before and after at least 3 months of omega-3 fatty acid supplementation). Time domain heart rate variability (HRV) and heart rate (HR) were examined for these patients. As a control, we used 24 h Holter ECG recordings of 94 nonobese children and adolescents. Time domain HRV parameters, which are indicators of vagal stimulation, were significantly lower in obese patients than in healthy controls, but HR was higher (standard deviation of the normal-to-normal [SDNN] interbeat intervals: −34.02%; root mean square of successive differences [RMSSD] between normal heartbeats: −40.66%; percentage of consecutive RR intervals [pNN50]: −60.24%; HR: +13.37%). After omega-3 fatty acid supplementation, time domain HRV parameters and HR of obese patients were similar to the values of healthy controls (SDNN interbeat intervals: −21.73%; RMSSD: −19.56%; pNN50: −25.59%; HR: +3.94%). Therefore, omega-3 fatty acid supplementation may be used for cardiovascular prophylaxis in obese children and adolescents.